Book review: Queer Interviews - New Directions and Various Challenges. Clare Summerskill, Amy Tooth Murphy, and Emma Vickers: New Directions in Queer Oral History. Archives of Disruption. 2022. ISBN 978-0-367-55113-1 - Lukkarinen Jean (Finland, 2025)
New Directions in Queer Oral History is an incredibly detailed collection of 19 articles from queer oral historians with various backgrounds. In their articles, the writers revisit their queer history interviews and discuss the difficulties and possibilities that queer oral history has as a practice. The book also gives tools for its readers to prepare for different kinds of obstacles they might discover while interviewing sexual and gender minorities. In this book review, I discuss themes of the book and reflect on them in relation to my own oral history interviews in my MA project on Finnish trans history.